PENGEMBANGAN MEDIA PEMBELAJARAN MENGGUNAKAN CAPASITIVE SENSOR DAN ARDUINO UNO - Retno Wahyusari; Lastoni Wibowo (LPPM STMIK Lombok, 2021)
Education is a lifelong process. The education process is carried out at the age of 0 to 6 years, is an early childhood education. Early childhood has a short concentration time, so media is needed that can maintain children's concentration. Learning media is a medium used to increase the concentration of early childhood in learning. The development of learning media is very possible by combining various technologies. Technologies that can be used in the development of learning media are Arduino microcontrollers and capacitive sensors. The Arduino microcontroller functions to send information or input and convert it into output. The input received on the learning media is in the form of a capacitive sensor, the output produced is in the form of sound produced by Audio Shield through the speaker. Learning media is in the form of learning media to recognize cow body parts, flat shapes and means of transportation. The test results show that the capacitive sensor and Arduino Uno can work well in responding to touch and playing sound according to the material in the learning media. The learning media made are able to provide alternative teachers in explaining the material and attracting students' interest, this is due to the sound response produced by the learning media.